Brief COPE-26 Coping Scale: Ukrainian-Language Adaptation and Modification for Online Diagnostics - Aleksina Nadiia; Lavrynenko Denys; Savchenko Olena; Gerasimenko Olga (Insight: the psychological dimensions of society, 2024)
The study of psychological resources for overcoming stress is one of the most urgent tasks of psychological science and practice during the war, which requires the development of appropriate psychometric tools. The purpose of the article is to analyze the psychometric properties of the Brief-COPE questionnaire and develop a scientific discussion of its factor structure. Methods. Two bilingual psychologists were involved in the direct and back translation of the methodology and three experts in psychology, English and Ukrainian philology evaluated the Ukrainian version. To test the psychometric properties of the methodology, a sample of civilian Ukrainians aged 17 to 75, totaling 1101 people, was formed. Based on the results of the testing, it was decided to exclude two items of the distraction scale that impaired the psychometric quality of the questionnaire. The shortened version of the Brief-COPE-26 has high internal consistency and retest reliability. The convergent validity is confirmed by correlations with other scales that assess human behavior in a stressful situation: the level of emotional acceptance, social distancing, mental health assessments, and the severity of generalized anxiety. The close relationship between the results of the Brief-COPE-26 and the COPE dispositional questionnaire indicates the completeness of the reflection of the measured phenomenon. The factor structure of the scales is not perfect, but it is similar to the original author’s model and the results of factorization obtained in other cultural adaptations. The search for the optimal structure that best matches empirical reality led to the identification of a five-factor model that included 11 scales: problem-focused actions and reasoning (active coping); reconciliation with the existence of the problem (passive coping); comprehensive social support, including venting negative feelings (collective coping); helplessness and humor. This structure may reflect the peculiarities of the Ukrainian population’s coping with chronic stress caused by a full-scale war. Discussion and conclusions. The Brief-COPE is an informative, valid, and reliable tool for measuring a wide range of individual reactions to stress. Its methodological advantage is the flexibility of application in accordance with the goals and conditions of the study, which is achieved by modifying the instructions, formulations, and a set of measuring scales.